Interpretación de la competitividad de la sanseviera con la metformina como un hipoglucemiante en la diabetes mellitus tipo 2 - Pallo Pilalumbo, Misshel Gissela (2025)
Diabetes mellitus type II is a metabolic disorder of high incidence worldwide characterized by elevated blood glucose levels due to the reduction in its production by the β-cells of the pancreas, being associated in the long term with the deterioration of several organs. Objective: to interpret the competitiveness to evaluate and compare the efficacy of Sansevieria with metformin as a hypoglycemic in the treatment of type 2 diabetes mellitus, analyzing its relative ability to control blood sugar levels through a literature review. Methodology: focused on a literature review using a qualitative approach. This study was based on an interpretative analysis from the researcher's perspective, using various data collection techniques. To conduct the review, a period of analysis was defined from 2018 to 2023. Studies were selected that provided empirical data, critical analyses, and theoretical reviews on the competitiveness of Sansevieria compared to metformin. Theoretical methods such as the analytical-synthetic method were used to decompose and review the literature, integrating the information to discover relationships and general characteristics. Inclusion and exclusion criteria were established to ensure the scientific quality and relevance of the studies. Results: Although Sansevieria has shown hypoglycemic potential in preclinical studies, metformin remains the preferred choice due to its proven efficacy and well-established safety profile. To consider Sansevieria as a viable alternative, further clinical investigations are required to confirm its efficacy and safety in humans.